Exploration of Human Resource Challenges Faced by the Teachers in Transferring Training - Suleiman, Wasilu; Adamu, Muhammad; Inuwa, Mohammed (International Journal of Business and Management Future, 2017)
Organizations hope that their employees are able to learn and acquire new knowledge and skills in the events of training and effectively transferring it back to the workforce, but it is deteriorating day by day. This paper explores challenges faced by trainees in transferring training through focus group interviews. Content analysis was the procedures and techniques employed to analyze the gathered data. The findings uncover and highlighted some major challenges that hinder employees to properly transfer what they might have learned in the training session on their jobs. The ability of the management to overcome those challenges would drive workers to be them to be desirous in making persistent and intense efforts towards utilizing skills and knowledge learned in the work settings. Human resource trainers need to overcome the identified challenges on employees’ training transfer in the organization.